Efficacy of repeated ovum pick-up in Podolic cattle for preservation strategies: a pilot study. Issue 1 (14th December 2020) - Presicce, Giorgio Antonio; Neglia, Gianluca; Salzano, Angela; Padalino, Barbara; Longobardi, Valentina; Vecchio, Domenico; De Carlo, Esterina; Gasparrini, Bianca
Abstract: The study evaluated the effects of eCG treatment prior to ovum pick up (OPU) on follicular population, oocyte and embryo yields in summer and autumn in Podolic cattle. The effects of repeated OPU on cattle wellbeing was also documented. Twenty-six animals were used, and split into two groups, treatment (OPU; n = 18) and control (CG; n = 8). The OPU cattle were subsequently split into two subgroups ( n = 9) and underwent repeated OPU, without and with eCG priming, for a total of 8 sessions (4 sessions/season). Follicular population, oocyte and embryo yields were recorded in those sub-groups. CG was handled in the same manner of OPU, except for epidural anaesthesia and follicular aspiration. Biochemical profile, serum protein electrophoresis and haptoglobin levels were analysed in OPU and CG. Hormonal priming increased the number of medium follicles (1.7 ± 0.2 vs 0.9 ± 0.2, p < .05), while it decreased the recovery rate and number of cumulus-enclosed oocytes (COCs) (recovery rate: 38.3 ± 3.5 vs 60.5 ± 4.0%; COCs: 2.3 ± 0.3 vs 3.4 ± 0.4, respectively; p < .01). However, priming increased cleavage (72.9 ± 5.7 vs 49.4 ± 5.4; p < .05) and blastocyst (41.1 ± 5.7 vs 23.0 ± 4.2; p = .054) rates. With regard to season's effect, a higher number of COCs was recorded in autumn than in summer (3.1 ± 0.4 vs 2.6 ± 0.3; p < .05) without affecting though the number of embryos produced (0.9 on average). Since haematological parameters did not vary between OPU and CG, our preliminary data suggest that repeated OPU may be used as a conservation strategy in Podolic cattle without affecting wellbeing. Highlights: Podolic cattle is an endangered Italian breed, reared in semi-extensive/extensive systems Ovum pick-up (OPU) can be carried out in this breed without impairing animal health and welfare The eCG treatment before OPU (priming) did not improve the number of embryos produced per donor.